Calendars in the making : the origins of calendars from the Roman Empire to the later Middle Ages - Stern, Sacha (Time, astronomy, and calendars ;, 2021)
"Calendars in the Making investigates the origins of calendars we are most familiar with today, yet whose early histories, in the Roman and medieval periods, are still shrouded in obscurity. It examines when the seven-day week was standardized and first used for dating and time reckoning, in Jewish and other constituencies of the Roman Empire; how the Christian liturgical calendar was constructed in early medieval Europe; and how and when the Islamic calendar was instituted. The volume includes studies of Roman provincial calendars, medieval Persian calendar reforms, and medieval Jewish calendar cycles. Edited by Sacha Stern, it presents the original research of a team of leading experts in the field. Contributors are: François de Blois, Ilaria Bultrighini, Sacha Stern, Johannes Thomann, Nadia Vidro, Immo Warntjes"--